Effect of Enterococcus Faecalis Bacteria and Calcium Lactate on Concrete Properties and Self-Healing Capability - Juki, Mohd Irwan; Anneza, L.H.; Othman, N. (International Journal of Sustainable Construction Engineering and Technology, 2019)
The objective of this study was to determine the effect of concrete properties and self-healing capability of bacteria and calcium lactate in concrete. The bacteria used in this study is locally isolated from fresh urine. The novelty of this study is the enrichment and method the bacteria and calcium lactate is added into concrete. Bacterium is isolated, enriched and identified using PCR and DNA sequencing. Mechanical properties tests such as compressive, flexural and tensile strength test were conducted. Self-healing capabilities of the concrete were tested using UPV and stereomicroscope. SEM and EDX was conducted to verify and confirm the bacteria precipitation of calcium carbonate. It was found that 2.18 g/L of calcium lactate with 3% Enterococcus faecalis increase the compressive strength from 36 MPa (Control) to 39.6 MPa. The flexural strength test achieved 6.72 MPa from 4.78 MPa. This increase in mechanical properties was possibly due to calcium carbonate formed due to the bacteria ability to precipitate calcium carbonate through urease enzyme. This was confirmed through SEM and EDX. This calcium carbonate formation is directly responsible for self-healing capabilities analyzed through UPV and stereomicroscope.